STUDENTS’ PERCEPTIONS TOWARD TEACHER’S TALK IN EFL CLASSROOM OF INDONESIA SENIOR HIGH SCHOOL: A CASE STUDY - ERLY MULFIAS YULI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This study is a case study to investigate students’ perceptions toward teacher’s talk in EFL (English as a Foreign Language) classrooms. It is conducted for two months on a single entity as the research subject, ie on 35 Eleventh-graders with varying English language skills and an English teacher. Since it focuses only on a certain entity, the results of the study cannot be generalized to the broader context. This study uses a qualitative approach by showing data from the results of questionnaires, observations and interviews with research samples. The study focuses on a research question on how Eleventh graders' perception on a teacher’s talk in EFL classrooms. Regarding to the research question, it aims to determine the thoughts of students on teacher’s talk, so that the teacher can organize and modify the class based on the perceptions that can implicate the learning process by reducing students’ anxiety. It provides students opportunities to be able to process information or lessons learned more comfortably, thus it reduces obstacles in learning. The findings of the study show that the majority of students of Eleventh-grade want to fully use English although they still have difficulties in understanding and feel less confident in using English.